Effects of β-Carotin and Green Tea Powder Diets on Alleviating the Symptoms of Gouty Arthritis and Improving Gut Microbiota in C57BL/6 Mice - Feng, Yu; Yu, Yanbo; Chen, Zheng; Wang, Lili; Ma, Jingyu; Bai, Xiaohui; Sun, Yundong; Wang, Dawei (Frontiers in Microbiology, 2022)
As a chronic metabolic disease caused by disorders of purine metabolism, gout has shown increasing incidence rate worldwide. Considering that gout is not easily treated and cured, further studies are explored to prevent gout development through diet modification. Both β-carotin and green tea powder are rich in dietary fiber, which helps maintain the balance of gut microbiota in humans. The aim of this study was to investigate the effects of β-carotin and green tea powder diet on the prevention of gouty arthritis in relation to the bacterial structure of gut microbiota in mice. We successfully induced gouty arthritis in C57BL/6 mice by injecting monosodium urate (MSU) crystals and feeding high-fat diet (HFD), and further investigated the effects of additional β-carotin and green tea powder in the diets of mice on the prevention of gouty arthritis in mice. Our results showed that diet of β-carotin and green tea powder reduced the joint swelling and pain in mice with gout, reduced the levels of serum uric acid and three types of pro-inflammatory cytokines, i.e., interleukin-1β, interleukin-6, and tumor necrosis factor-α, improved the gut microbiota, and reduced the metabolic levels of purines and pyrimidines. In conclusion, our study provided evidence to support the application of β-carotin and green tea powder diet as a dietary adjustment method to prevent and treat gouty arthritis.